STUDI KELAYAKAN TAMBAK UNTUK BUDIDAYA RUMPUT LAUT (Gracilaria sp) DI DESA PANYIWI KECAMATAN CENRANA KABUPATEN BONE - Amir, Muh Riski (Jurnal Environmental Science, 2019)
ABSTRACT                This research is a survey research that aims to determine the characteristics and level of feasibility of ponds for seaweed cultivation (Gracilaria sp) based on physical parameters (temperature, salinity, depth, brightness, phosphate, type of substrate, tidal amplitude and protection) and chemistry (pH, dissolved oxygen, Nitrate). The population in this study was the existing pond area in Panyiwi Village, Cenrana Subdistrict, Bone Regency, the sample as many as 8 points / observation station was determined using purposive sampling method based on the location and water source of the pond. Data collection time is done twice, morning and evening. Research data obtained by observation, direct measurements in the field (temperature, salinity, depth, brightness, dissolved oxygen, pH and protection) and laboratory analysis (phosphate, nitrate, and substrate type) were then analyzed using the weighting method. After obtaining the score value of each parameter at each observation point, then the assessment is feasible (S1) with a range of 68-87, quite feasible (S2) with a range of 48-67, and not feasible (N) with a range of 27- 47. So that obtained the results of each station in the morning, stations I, II, III, IV, V, VI, VII, VIII entered in quite decent categories (S2) and each station in the afternoon namely stations I, II, III, V , VI, VII, VIII also included in the category of quite feasible (S2) except on station IV it was in the category of not feasible (N) dry ponds due to low tide.